Impact of Plant Growth Promoting Bacteria on Salicornia ramosissima Ecophysiology and Heavy Metal Phytoremediation Capacity in Estuarine Soils - Mesa-Marín, Jennifer; Pérez-Romero, Jesús A.; Redondo-Gómez, Susana; Pajuelo, Eloísa; Rodríguez-Llorente, Ignacio D.; Mateos-Naranjo, Enrique (Frontiers in Microbiology, 2020)
Salicornia ramosissima is a C3 halophyte that grows naturally in South Western Spain salt marshes, under high soil salinity and heavy metal pollution levels caused by both natural and anthropogenic pressure. However, very few works have reported the phytoremediation potential of S. ramosissima. In this work, we studied a microbe-assisted phytoremediation strategy under greenhouse conditions. We inoculated heavy metal resistant Plant Growth Promoting Bacteria (PGPB) in pots with natural non-polluted and polluted sediments collected from Spanish estuaries and S. ramosissima. Then, we analyzed plant ecophysiological and metal phytoaccumulation response to heavy metal pollution and bacterial inoculation. Our data suggested that, at the end of the experiment (30 days), inoculation improved S. ramosissima plant growth in terms of relative growth rate and number of new branches in both sediments. S. ramosissima photosynthetic fitness was affected by heavy metal presence in soil, but bacteria inoculation improved the integrity and functionality of the photochemical apparatus, as reflected by increments in values of net photosynthetic rate, functionality of PSII and electron transport rate. Beneficial effect of bacteria was also observed by augmentation of intrinsic water use efficiency and water content in inoculated S. ramosissima. Finally, our results demonstrated that S. ramosissima was able to accumulate great concentrations of heavy metals, mostly at root level, up to 200 mg Kg-1 arsenic, 0.50 mg Kg-1 cadmium, 400 mg Kg-1 copper, 25 mg Kg-1 nickel, 300 mg Kg-1 lead and 300 mg Kg-1 zinc. Bioaugmentation incremented S. ramosissima heavy metal phytoremediation potential due to plant biomass increment achieved after inoculation, which enabled a greater accumulation capacity. Thus, our results suggest the possibility of using heavy metal resistant PGPB inoculation to reinforce the potential of S. ramosissima to be used as candidate species in phytoremediation of salty degraded ecosystems.